Adaptation of the State Trait Anxiety Inventory (STAI-Y) Using Confirmatory Factor Analysis (CFA) - Veda Salsabila, Malva; Ichsano, Alghifari; Ulwan, Muhammad Yazid; Allysa, Annisa Mahqdis; Malik, Muhammad Rafi (ANFUSINA: Journal of Psychology, 2026)
State anxiety arising from concerns about Grade Point Average (GPA) requirements may affect students’ well-being and academic performance, highlighting the need for culturally valid and contextually adaptive measurement instruments. This study aimed to adapt and examine the psychometric properties of the abbreviated State-Trait Anxiety Inventory Form Y-1 (STAI-Y1) for assessing students’ state anxiety regarding their GPA. The adaptation process consisted of forward translation, synthesis, back-translation, harmonization, and a readability assessment (Aiken’s V = 0.73). Data were collected through an online questionnaire from 202 students aged 18–25 years in West Java, Indonesia. Construct validity was evaluated using Confirmatory Factor Analysis (CFA) based on a unidimensional model. The initial eight-item model demonstrated poor fit. Model respecification involved removing Items 1 and 5 due to low factor loadings and redundancy, as well as adding residual correlations between semantically similar item pairs (Items 3–7 and 6–8). The resulting six-item model demonstrated good model fit (CFI = 0.969; TLI = 0.933; GFI = 0.964; SRMR = 0.049). Although the ratio of favorable to unfavorable items became unbalanced, the six-item structure demonstrated adequate validity, reliability, and statistical parsimony for assessing students’ state anxiety regarding GPA. This adapted instrument may be useful for educational psychology research and academic intervention programs. Keywords: Instrument Adaptation, Confirmatory Factor Analysis, Anxiety, University Students, STAI-Y1